Endoscopy-assisted resection of a sphenoid-wing meningioma using a 3D-printed patient-specific pointer in a dog: A case report - So, JaeWon; Lee, HaeBeom; Jeong, JaeMin; Forterre, Franck; Roh, YoonHo (Frontiers in Veterinary Science, 2022)
A 9-year-old female mixed-breed dog presented for treatment of a presumed sphenoid-wing meningioma. Clinical signs included tonic-clonic seizures lasting less than 1 min, which had started three months previously. The physical examination results were unremarkable. An eccentrically located neoplastic cystic structure in the right sphenoid bone region suggestive of a meningioma and peritumoural brain oedema was observed in preoperative magnetic resonance imaging (MRI). Prior to surgery, a three-dimensional (3D) patient-specific pointer (PSP) was designed using computed tomography (CT) images and computer-aided 3D design software. After a targeted approach and exposure of the lateral part of the right temporal lobe by a craniectomy guided by the 3D-PSP, complete macroscopic piecemeal resection of the meningioma could be performed using endoscopy-assisted brain surgery. Post-operative MRI confirmed complete excision of the tumour. Anticonvulsive therapy was discontinued after 90 days, and the dosage of anticonvulsants was tapered two weeks after surgery. At a follow-up examination 225 days postoperatively, recurrence of seizures was not observed, and the absence of tumour recurrence was confirmed by a repeat MRI examination. To the best of our knowledge, this is the first report in veterinary medicine describing a successful resection of a sphenoid-wing meningioma using a 3D-PSP. 3D-PSP-assisted craniectomy may be a surgical option for some canine skull-based tumours, such as sphenoid wing meningiomas.